5.PATTERN AND DETERMINANTS OF PSYCHOGERIATRIC DISORDERS AMONG THE ATTENDEES OF OLD AGE PSYCHIATRIC UNIT, BAGHDAD, IRAQ (Iraqi Journal of Medical Sciences, 2018)
Background: Mental disorders in old age are frequent.Objective: To determine the diagnostic pattern of mental disorders in elderly patients aged ? 60 years, attending the Old Age Psychiatry Unit, Ibn-Rushed Psychiatric Teaching Hospital, Baghdad, Iraq.Methods: A retrospective study to all attendees to the Old Age Psychiatry Unit between January 2009 and November 2011 was carried out. Data collected included diagnoses, comorbid disorders, treatment received, and socio demographic characteristics. Results: Analysis of 907 patients was done; the mean age 68 ± 6.3 years, 67.5% age range 60 – 69 years, 70% married, 50% without income (unemployed and housewives), 52% illiterate, and 98.5% live with their families. Depression was 46.9%, schizophrenia 23.2%, and 20.7% dementia. 48% of clients had comorbid illness. All patients had at least one pharmacological medication. Diagnoses high statistical significant association with gender (P=0.000), marital status (P=0.001), occupation (P=0.000), and education level (P=0.000).Conclusion: Mental disorders in old age are frequent. Many old age people were with limited access to mental health services. Mental health services must be designed to meet the needs of older people at all points of the mental health continuum.Keywords: Pattern, determinants, elderly, psychiatry, IraqCitation: Al Abbudi SJR, Ezzat KI. Pattern and determinants of psychogeriatric disorders among the attendees of Old Age Psychiatric Unit, Baghdad, Iraq. Iraqi JMS. 2018; Vol. 16(1): 22-29. doi: 10.22578/IJMS.16.1.5
Keywords: Pattern; determinants; elderly; psychiatry; Iraq